FAKTOR RISIKO APNEA TIDUR OBSTRUKTIF YANG DAPAT DIMODIFIKASI - Kemal Akbar Suryoadji (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
Background: Obstructive sleep apnea, also known as OSA (obstructive sleep apnea), is a sleep disorder in the form of a recurring complete or partial collapse of the airway. The prevalence of obstructive sleep apnea in America is 14% in men and 5% in women. The population in Asia is also a risk factor for obstructive sleep apnea. Methods: The literacy scan used 14 most recent and reliable international journals to describe modifiable risk factors for obstructive sleep apnea. Discussion: Obstructive sleep apnea is associated with other diseases such as cardiovascular, metabolic, and neuropsychiatric disorders. There are three important aspects that are modifiable risk factors for obstructive sleep apnea, including ideal body weight, namely to maintain a body mass index of less than 25 kg / m2, optimal physical activity by doing aerobic physical exercise for 150 minutes per week. , and reduce consumption of cigarettes and alcohol. Conclusion: Modifiable risk factors for obstructive sleep apnea include ideal body weight, physical activity, and consumption of cigarettes and alcohol. These factors can be used as a solution and prevention in obstructive sleep apnea to also avoid symptoms and other related diseases.